A Qualitative Evaluation of the Acceptability of a Tailored Smartphone Alcohol Intervention for a Military Population: Information About Drinking for Ex-Serving Personnel (InDEx) App - Puddephatt, Jo-Anne; Leightley, Daniel; Palmer, Laura; Jones, Norman; Mahmoodi, Toktam; Drummond, Colin; Rona, Roberto J; Fear, Nicola T; Field, Matt; Goodwin, Laura (JMIR Publications, 2019)
BackgroundAlcohol consumption in the UK Armed Forces is higher than in the general population, and this pattern continues after leaving the service. Smartphone apps may be useful to increase ex-serving personnel's awareness of their alcohol consumption, support self-monitoring, and prompt a change in behavior. ObjectiveThe study aimed to explore the acceptability of Information about Drinking in Ex-serving personnel (InDEx), a tailored smartphone app, combined with personalized short message service (SMS) text messaging designed to target ex-serving personnel who meet the criteria for hazardous alcohol use. MethodsThe InDEx intervention included 4 key modules: (1) assessment and normative feedback, (2) self-monitoring and feedback, (3) goal setting and review, and (4) personalized SMS text messaging. A semistructured telephone interview study was conducted with ex-serving personnel after using the app for a 28-day period. Interviews were used to explore the acceptability of app modules and its functionality and the perceived changes in participant's drinking. Interview transcripts were analyzed using inductive thematic analysis. ResultsOverall, 94% (29/31) participants who used InDEx agreed to take part in a telephone interview. Overall, 4 themes were identified: Credibility, Meeting their needs, Simplicity, and Helpful for ex-serving personnel. The importance of credibility, functionality, and meeting the individual needs of ex-serving personnel was emphasized. Acceptability and engagement with specific modules of the app and text messages were influenced by the following: (1) if they felt it provided credible information, (2) whether the content was appropriately personalized to them, (3) the ease of use, and (4) beliefs about their own drinking behaviors. Participants recommended that the app would be most suitable for personnel about to leave the Armed Forces. ConclusionsInDEx was an acceptable smartphone app for ex-serving personnel for monitoring alcohol consumption and in providing meaningful feedback to the individual. Pages that met the participant's interests and provided real time personalized, credible feedback on their drinking and text messages tailored to participant's interactions with the app were particularly favored.